IMPROVING STUDENTS’ LEARNING OUTCOME: IMPLEMENTATON MIND MAPPING METHOD WITH GOCONQR - Dewi Dewantara (Program Studi Pendidikan IPA, Fakultas Ilmu Pendidikan, Universitas Trunojoyo Madura, 2019)
This article aims to describe the improvement in student learning outcomes after applying to learn with the mind mapping method using the GoConqr application. This type of research is a quantitative descriptive. The sampling technique was purposive sampling, namely students who took the